Design of a Single-Layer Frequency Selective Surface for 5G Shielding - Qu, Meijun; Feng, Yunfei; Su, Jianxun; Shah, Syed Mohsin Ali (IEEE microwave and wireless components letters, 2021)
In this letter, a single-layer bandpass frequency selective surface (FSS) working at 2.6 GHz is proposed to decrease the interference to communication systems and the cost of processing based on a multimode resonator. A metasurface unit cell is adopted to suppress the grating lobe and achieve miniaturization. Therefore, the performance of the proposed FSS can remain stable under a large oblique incidence. The surface current distribution and equivalent circuit model at each design step are extracted to explain its working principle. Good agreement between the experimental results and the simulated response verifies the feasibility of the proposed FSS.